The hungry girl diet cookbook : healthy recipes for mix-n-match meals & snacks - Lillien, Lisa (St. Martin's Griffin, 2015)
"In ... The Hungry Girl Diet, Lillien served up the first-ever diet plan utilizing the ... Hungry Girl philosophy and recipe concepts. Now she's back with 200 ... new recipes that fit perfectly into the plan. ... With an emphasis on lean protein, fresh fruits 'n veggies, big portions, and craving-busting dishes, this book gives you everything you love about Hungry Girl in a weight-loss-centric cookbook--